A design for a generic and modular bio-economic farm model. (June 2021) - Britz, Wolfgang; Ciaian, Pavel; Gocht, Alexander; Kanellopoulos, Argyris; Kremmydas, Dimitrios; Müller, Marc; Petsakos, Athanasios; Reidsma, Pytrik
Abstract: Context: Past reviews of policy impact assessment studies using bio-economic farm models (BEFM) called for the development of a generic and modular implementation that can be maintained by a network of modellers. A main reason for these calls is the project-oriented way in which model developers receive funding. It favours the development of new models with case-study specific features over the maintenance and extension of well-tested, more generic ones which allow comparing results in a consistent way across many case-studies. The demand for more generic tools also reflects the dynamic landscape of policy measures within larger policy frameworks like the Common Agricultural Policy (CAP). These policy frameworks move increasingly away from a 'one-size-fits-all' approach of policy design towards more flexible systems, giving greater freedom to shape, implement, and target policy measures to specific regions, farm management systems and farm types. This creates new challenges for model-based impact assessment as applied models have to reflect the variety of policy measures and characteristics of targeted farmers and rural communities. Objective: The aim of this paper is to first address key questions regarding the functionality and implementation of such a modular BEFM that can be maintained and expanded by a user group, and second to develop concrete proposals of necessary model features, model design and shared development. Methods: This paper builds on literature research, including a detailed review of four models that are used extensively for impact assessment within the EU and were developed by multiple teams over a longer period of time. From there, necessary and desirable features of a generic and modular BEFM are identified and requirements for model design regarding modularity, software engineering, and shared development are discussed. Results and conclusions: This feeds into the development of concrete proposals of how modularity and flexibility can be addressed in the development, application and maintenance of a BEFM. At the end, a list of design decisions and implementation steps is proposed to build a modular BEFM that can be maintained by a network of researchers. Significance: The concept for a network-based generic and modular bio-economic farm model responds to the demand for analytical tools in agricultural policy impact analysis. The paper develops a research agenda to overcome observed limitations in the current landscape of such models. Graphical abstract: Unlabelled Image Highlights: Case-study driven bio-economic farm model development slows methodological progress. This motivates a network-based and modular approach for a generic bio-economic farm model. Four applied models are reviewed in detail and desired features of a generic one are derived. Details of a generic and modular implementation of desired model features are developed. This yields a concept for a network-based generic and modular bio-economic farm model.